Clinical examination findings as predictors of acute kidney injury in critically ill patients - Wiersema, Renske (Acta Anaesthesiol Scand, 2019)
BACKGROUND: Acute Kidney Injury (AKI) in critically ill patients is associated with a markedly increased morbidity and mortality. The aim of this study was to establish the predictive value of clinical examination for AKI in critically ill patients. METHODS: This was a sub‐study of the SICS‐I, a prospective observational cohort study of critically ill patients acutely admitted to the Intensive Care Unit (ICU). Clinical examination was performed within 24 hours of ICU admission. The occurrence of AKI was determined at day two and three after admission according to the KDIGO definition including serum creatinine and urine output. Multivariable regression modeling was used to assess the value of clinical examination for predicting AKI, adjusted for age, comorbidities and the use of vasopressors. RESULTS: A total of 1003 of 1075 SICS‐I patients (93%) were included in this sub‐study. 414 of 1003 patients (41%) fulfilled the criteria for AKI. Increased heart rate (OR 1.12 per 10 beats per minute increase, 98.5% CI 1.04‐1.22), subjectively cold extremities (OR 1.52, 98.5% CI 1.07‐2.16) and a prolonged capillary refill time on the sternum (OR 1.89, 98.5% CI 1.01‐3.55) were associated with AKI. This multivariable analysis yielded an area under the receiver‐operating curve (AUROC) of 0.70 (98.5% CI 0.66‐0.74). The model performed better when lactate was included (AUROC of 0.72, 95%CI 0.69‐0.75), P = .04. CONCLUSION: Clinical examination findings were able to predict AKI with moderate accuracy in a large cohort of critically ill patients. Findings of clinical examination on ICU admission may trigger further efforts to help predict developing AKI.